FACTORS THAT INFLUENCE THE TIMELINESS OF PUBLICATION OFFINANCIAL STATEMENTS ON BANKING IN INDONESIA - Galuh Hesti Wulandari (TECHNOBIZ : International Journal of Business, 2018)
The purpose of this study is to examine the effect of financial ratios, firm age, firm size, and auditor's opinion on the timeliness of publication of banking financial statements listed on the Indonesia Stock Exchange (IDX). The population in this study were 87 banking companies during the period 2010-2012. The number of sample companies in this study is 29 companies. Samples were taken based on purposive sampling method. Data were analyzed using logistic regression technique.The results showed that the variable financial ratios have a significant positive effect on the timeliness of the publication of financial statements. The variable of firm size has significant influence, but has negative direction to the timeliness of publication of financial report, while the variable of firm age and auditor’s opinion does not affect the timeliness of publication of financial report.